The influence of factors on the development of a civic society with a cultural environmental perspective in river communities In Banjarmasin city - Wahyu, Wahyu; Heru Puji Winarso; Mariatul Kiptiah (Asean Study Center Lambung Mangkurat University, 2023)
Public madani by various parties more interpreted approach draft civil society. Essence basically is aware will important strengthening public in A community country For balance And controls state policies that tend to position society as the party that weak. In this case, it is also necessary to have parties who are directly involved in implementing activities to find out directly about social conditions so that policy makers and program implementers know what needs to be implemented and improved in the riverside community environment in Banjarmasin City. This research aims to examine and search for natural phenomena and obstacles in influencing factors in the development of a civic society with an environmental and cultural perspective in riverside communities. This research uses a qualitative approach through descriptive research methods: direct observation, interviews, documentation, and summarizing work completed in the field. The results of this research reveal the following: (1) internal factors include the fact that there are still many people on the riverbanks of Banjarmasin City who have lower middle class economies so paying waste money fees for officers is no longer difficult. The community needs assistance from the government in the form of business capital to grow the economy of the riverside communities of Banjarmasin City by providing adequate facilities and infrastructure in an effort to maintain and preserve environmental cleanliness and community welfare; (2) external factors in government policy regarding green village tourism, such as the existence of souvenir centers and art performances for tourism visitors so that they can help and strengthen the community economy and national economy with the help of river tourism icons.